American Jihad: The Terrorists Living Among Us by Steven Emerson (New York: Free Press, 2003. 285 pages.) (American Journal of Islam and Society, 2003)
"Terrorism expert" Steven Emerson has done it again. With his usual exaggeratedstyle and hate-mongering rhetoric, Emerson has painted allMuslims with the same broad brush. While trying to assure his readers atthe outset that not all Muslims are terrorists, the bulk of his new book,American Jihad, is filled with brazenly over-simplified attacks on the entireMuslim American community. This biased and heavy-handed portrayal ofMuslims is characteristic of Emerson's work - most notably his 1994 PBSvideo "Jihad in America." In American Jihad, Emerson again presents a terrifyingpicture of American Muslims as fanatical, violent people lurkingand plotting against the United States. It is thus hardly surprising that he hasgained a reputation, reminiscent of his friend Daniel Pipes, for advocatinggrand Islamic conspiracies without any credible evidence.In a rush to get to press, his latest book is a quick tabloid-style read.The book is divided into eight chapters. The first chapter deals withEmerson's "discovery" of"militant Muslims" and the subsequent makingof his PBS video "Jihad in America." The next six chapters attempt touncover the inner working of such groups as the Council on AmericanIslamicRelations (CAIR), Hamas, and al-Qaida. He also spends oneentire chapter on the terrorist infiltration of American academic institutions.Finally, in his concluding chapter, Emerson tries to encourage individualswithin the Muslim community to "fight back" against the threatthat he feels is facing the country.The book is large on print and short on analysis. For a decade,Emerson has been issuing dire, over-the-top warnings that Muslims in theUnited States pose a catastrophic threat to the country, and in this book ...